Proportion of incomplete preventive treatment and its associated factors among latent tuberculosis infection patients in Sabah - Mohamed, Ahmad Firdaus (2023)
Background: Latent tuberculosis infection (LTBI) is a major public health concern; almost a third of the world’s population is estimated to have LTBI. A significant proportion of infected individuals progress to active tuberculosis (TB), especially among the frequently exposed and immunocompromised groups. Completion of LTBI preventive treatment is crucial to prevent progression to active TB. Objective: This study aimed to identify the proportion of incomplete preventive treatment and its associated factors among LTBI patients in Sabah, Malaysia. Methods: A retrospective record review was conducted among LTBI patients registered in the Sabah State Health Department’s LTBIS 401A registry. This study utilized a retrospective cohort study design, using secondary data from the Sabah State Health Department's LTBIS 401A registry over four years, from January 2019 to July 2022. Data collection was conducted using a pre-designed proforma, and data were subsequently entered into a Microsoft Excel spreadsheet. Statistical analysis was performed using the SPSS version 26 software. Multiple logistic regression was used to determine the factors associated with incomplete LTBI preventive treatment. Results: A total of 895 LTBI patients were included in the study. The overall proportion of incomplete LTBI preventive treatment was 9.2%. Factors that were significantly associated with the incomplete preventive treatment were non-HCW occupation (OR=4.21, 95% CI: 1.25, 14.22), residents of Tawau Division (OR=2.00, 95% CI: 1.10, 3.65), and LTBI patients without contact to TB patients (OR=2.79, 95% CI: 1.42, 5.48). Conclusion: The proportion of incomplete preventive treatment among LTBI patients in Sabah was comparatively lower than in previously published studies. Targeted interventions should be developed to address the specific needs of the groups with higher odds of having incomplete LTBI preventive treatment. This includes tackling the Social Determinants of Health for example improving healthcare system accessibility and social gradient. Prospective studies should be conducted to evaluate these interventions' effectiveness in improving LTBI preventive treatment completion rates.